CHEMICAL AND BIOLOGICAL STUDY OF EUGENIA STIPITATA MC VAUGH COLLECTED IN THE COLOMBIAN ANDEAN REGION - Ãlvarez, Andree; JIMÉNEZ, ÁNGEL; MÉNDEZ, JONH; Murillo, Elizabeth (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of this study is to evaluate the chemical and bioactive properties of Eugenia stipitata (Myrtaceae) fruit seeds collected in the Andean region of Colombia using an ethanolic extract, a dichloromethane fraction (DF), and a hydroalcoholic residue. Methods: E. stipitata seeds were evaluated using bromatological analysis; these were macerated (ethanol 96%) and partitioned (dichloromethane). Phytophenols composition of the samples was tested by high-pressure liquid chromatography-mass spectrometry and Folin–Ciocalteu method, then calculated as gallic acid equivalents (GAEs). Antiradical capacity was tested by 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and 3-ethylbenzthiazoline-6- sulfonic acid (ABTS•+) and inhibitory concentration 50% (IC50) was calculated; antioxidant capacity was determined using ferric reducing antioxidant power, oxygen radical absorbance capacity, and OH• radical and hemolysis inhibition assays. Anthelmintic activity against Panagrellus redivivus and ovine gastrointestinal (GI) nematodes and toxicity on human blood cells were tested. Results: E. stipitata seeds contain protein, sulfur, boron, iron, and copper. The ethanolic extract exhibited significant anthelmintic activity against free-living and GI nematodes, which would be associated with the phytophenols content, mostly tannins (29.14 g GAE/100 g). DF displayed the highest antiradical capacity in DPPH• and ABTS•+ (IC50: 2.65 and 0.33 mg/l, respectively) methods, antioxidant capacity, and hemolysis inhibition of human erythrocytes (IC50: 200 mg/l). There were no toxic metabolites to human blood cells. Conclusion: These findings would be useful for promoting the use of E. stipitata seeds, collected in the Colombian Andean region, in biotechnological processes. This is the earliest paper showing a study carried out in Colombia with an interest in evaluating chemical and biological characteristics of E. stipitata seeds.